Pengaruh Latihan Box Jump dan Standing Jump Terhadap Tingkat Kemampuan Akurasi Tendangan Jarak Jauh Pemain Sepak Bola - Choirul Anas; Puriana, Ramadhany Hananto; Wahyono, Muhammad; Ado Aran, Kristoforus; Azmi, Khairul (Universitas Hamzanwadi, 2025)
This study aims to analyze the effect of box jump and standing jump training on the ability of long-distance kick accuracy of soccer players. The method used in this research is an experiment with a pretest-posttest control group design. The population in this study were 12 soccer players of SSB Kelud Sidoarjo. The research sample consisted of 12 soccer players who were taken using total sampling technique. Data analysis techniques use prerequisite tests in the form of normality tests, homogeneity tests, hypothesis tests. The results of the analysis showed that there was a significant increase in the ability of long distance kicks after the box jump training treatment, with an average increase of 8.10%. Meanwhile, standing jump training also shows an increase, but lower, which is 2.73%. The t-test shows that box jump training is more effective than standing jump training in improving long-distance kicking ability, with t count 3.163 > t table 2.228 and a significance value of 0.010 < 0.05. From the results of this study, it can be concluded that box jump training has a greater influence on improving the accuracy of long distance kicks compared to standing jump training.